2010
DOI: 10.1021/jp912139e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Graphene on Metals

Abstract: We use low-energy electron microscopy to investigate how graphene is removed from Ru (0001) and Ir(111) by reaction with oxygen. We find two mechanisms on Ru(0001). At short times, oxygen reacts with carbon monomers on the surrounding Ru surface, decreasing their concentration below the equilibrium value. This undersaturation causes a flux of carbon from graphene to the monomer gas. In this initial mechanism, graphene is etched at a rate that is given precisely by the same non-linear dependence on carbon monom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
111
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 29 publications
15
111
1
2
Order By: Relevance
“…The formed 1D etched trenches were exactly located at the bold wrinkles. Our finding is similar to the preferential oxidation of wrinkles at graphene/Ir(111) surface reported by Starodub et al 27 Besides the 1D trenches, many etched holes were also observed inside the graphene islands. We suggest that these holes may be attributed to oxygen etching of the wrinkles with nanometer scale, which can not be clearly imaged by LEEM.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The formed 1D etched trenches were exactly located at the bold wrinkles. Our finding is similar to the preferential oxidation of wrinkles at graphene/Ir(111) surface reported by Starodub et al 27 Besides the 1D trenches, many etched holes were also observed inside the graphene islands. We suggest that these holes may be attributed to oxygen etching of the wrinkles with nanometer scale, which can not be clearly imaged by LEEM.…”
supporting
confidence: 92%
“…26 Upon oxidation of graphene on metals, wrinkles showed different reactivity to the surface reaction compared to the flat graphene structure. 27 In the present work, an attempt was made to perform chemical reactions at graphene/Pt(111) surfaces, and the surface processes were dynamically imaged by low energy electron microscopy (LEEM). Both graphene oxidation and CO oxidation were found to occur underneath the graphene overlayers.…”
Section: Introductionmentioning
confidence: 99%
“…4a-c). The average size of the anti-dots shows a linear dependence with reaction time indicating that the etching process is controlled by oxidation kinetics 19,28 . STM imaging of the anti-dot, as shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…At high temperatures and oxygen pressure, macroscopic regions of graphene can be delaminated from oxidized Ru(0001) 18,19 . O 2 molecules can diffuse through step edges and surface defects 20 and permeate between graphene and ruthenium through the hump regions of the Moiré structures.…”
mentioning
confidence: 99%
“…These R s values were comparable to the detachment rate of C adatoms from the graphene on Ru (0.15 mm min À 1 ) at 1,070 K (ref. 44).…”
Section: Resultsmentioning
confidence: 99%